High circulation of pertussis in infants and close contacts in Antananarivo, the capital of Madagascar in Africa, and Cambodia in Asia - Gaelle Noel; Aina Harimanana; Laurence Borand; Florence Campana; Chanthy Leng; Chhunly Botr; Lala Rafetrarivony; Mahdi Rajabizadeh; Alexandra Kerleguer; Bunnet Dim; Anny M. Randriamoramanana; Mohand Ait-Ahmed; et al. (BMC Infectious Diseases, 2025)
Abstract Background Reliable data on whooping cough, a highly contagious disease sometimes fatal for infants, are largely lacking in low- and middle-income countries. Methods We conducted a hospital-based prospective study (PS) on infants, and a household contact-case investigation (CCI) for positive cases throughout Cambodia and in the city of Antananarivo, Madagascar, between 2017 and 2019. The PS, in which Bordetella diagnostics (qPCR) were performed, included infants aged ≤6 months presenting with ≥5 days of cough associated with one pertussis-like symptom. CCI was performed using qPCR and serology regardless of clinical signs. Results In this study, 207 and 173 participants from Cambodia and Antananarivo were respectively enrolled. Respectively 26.1% (54/207) and 22.0% (38/173) of the infants were infected in the cohorts from Cambodia and Antananarivo. Cough longer than 10 days appeared as a risk factor in both countries, as well as coughing spells, apnea and normal pulmonary auscultation, having a coughing contact in Cambodia. In Antananarivo, being clinically well between coughing spells appeared as a risk factor. Five infants, all positive, died during the study. In Cambodia and Antananarivo respectively, 50.9% (118/232) and 67.8% (82/121) of the contact cases were positive. Respectively 94.4% (51/54) and 90.3% (28/31) of the households had at least one positive contact case. Conclusion The data show that pertussis circulates at high levels among infants and in their households both in Cambodia and in Antananarivo. Given the vulnerability of youngest infants, who are too young to receive fully primary vaccination, they need to be protected through boosters breaking transmission chains. Molecular diagnosis, as well as trained medical human resources to detect the disease early, are absolutely key to protect populations.